Computer-aided chemical speciation in metal-based drug design - Nomkoko, Thembelani Edmund (Department of Chemistry, 2016)
Formation constants of Cu²⁺, Ni²⁺, Zn²⁺, Ca²⁺ and Gd³⁺ with the polyamine(amide) ligands N,N' -bis(2-hydroxyiminopropionyl) propane-1,3-diamine (L² ) and (1, 15)- bis(N,N-dimethyl)-5, 11-dioxo-8-(N-benzyl)-l ,4,8, 12, 15-pentaazapentadecane (L³ ) as well as those of Gd³⁺ with 3,3,9,9-tetramethyl-4,8-diazaundecane-2,10-dione dioxime (L 1 ) were investigated by glass electrode potentiometry at 25°C and an ionic strength (I) of 0.15 mol dm-³.